Shared intelligent optimum route selection through traffic management system in VANET SIRS - B Wagh, Mukund; Gomathi, N. (International Journal of Engineering and Technology, 2017)
A Vehicular Ad-hoc Network (VANET) consists of the vehicle to vehicle and vehicle to roadside communication. Growing the density of the vehicles on the road causes flooding while transferring packets from a source to one or multiple destinations over a VANET. However, increasing vehicles on road may causes a problem such as redundancy, congestion, collision and increasing delay though receiving emergency warnings. As long as reliable and proficient multi-hop broadcast in vehicular ad hoc networks is challenging one. In the proposed system commence a new protocol which uses the character of elegant route establishment and selection method for transfer information to the destination (dst) with minimum redundancy, delay and highest bits per second delivery. In some environment vehicles are deployed in a dense manner, and it can move at a high speed. Adjacent Access Points (APs) on the road find out route information from their past report gatherings which use a fuzzy logic to select routing conclusion. This approach consists of isolating the whole network area into clusters. Based on which an optimized route is chosen using the input parameters as vehicle density, distance from the adjacent AP, vehicle mobility, receiving signal strength and delay should be jointly measured in the relay node selection. Though, these computation conflicts with each other depend on vehicle mobility. Hence, we employ fuzzy logic to handle this imprecise information to select forwarding vehicles by mutually taking into account of vehicle distance (d), mobility (v) and Receiving Signal Strength (RSS). The selected vehicle can provide an assure data forwarding with a high competence. The performance of the proposed scheme is evaluated on the metrics such as end-to-end delay, packet delivery ratio by varying vehicle speed, and density of vehicles.
Keywords: Fuzzy Optimized Forward Node Selection; Performance evaluation; Routing; Redundancy; Vehicular Sensor Networks (VSNs).